PERCEPATAN WAKTU PELAKSANAAN PEKERJAAN KONSTRUKSI DENGAN METODE CPM DAN TCTO - Oktaviani, Cut Zukhrina; Majid, Ibnu Abbas; Risdiawati, Risdiawati (Universitas Bengkulu, 2019)
Construction delays are a common and major concern in most construction projects. Construction project delay can indirectly affect of project performance. Delay resolve method is to schedule crashing with various methods. This crashing planning is done by combining the Critical Path Method (CPM) and Time-Cost Trade-Off (TCTO) method for the minimum cost in crash duration calculation. Project A data is used to be a case studi in crash duration calculation and costs increase. Rescheduling with CPM result project completion time 120 days and after crashing project duration becomes 94 days, there was a reduction 26 days project completion time. Crashing programme are do to 18 activities from 30 critical activies rescheduling with CPM result. Total project costs changes is Rp. 19.923.466,- due working time addition (overtime) to reduce project time with Time Cost Trade Off method. Normal condition project costs is Rp. 985,171,182.52 and after duration crash becomes Rp. 1,005,094,648, -.